Country Brand, A Support Instrument In The Internationalization Of Colombian Companies (Journal of Namibian Studies : History Politics Culture, 2023)
This article aimed to analyze the relationship between the use of the country brand and the internationalization processes of companies in Colombia. To this end, it was sought to know the current concepts around the Country Brand, for which, a documentary review was carried out, through consultation in scientific databases such as Ebsco, Scopus, Jstor, Scielo, among the main ones, to make the collection of articles in theoretical aspects on the use of brand as a differentiating factor of positioning in the countries and referents from case studies of successful countries in your brand building. Similarly, a survey-type tool is applied, based on a database of companies allied to the country brand Colombia of a total of 140 exporting companies of which 34 companies answered the questionnaire. The database is provided by Procolombia. Among the main findings is that there is still a lot of ignorance of certain potentials that are faced with international markets. It also reflects the recognition that businessmen give in the face of the lack of preparation of people to face challenges in the international arena and how it is the duty of the state to strengthen public policies in education for the preparation of qualified personnel in negotiation and foreign trade issues.